Studies On Mold Extracts As Potential Therapeutic Agents For Hepatitis C And Dengue Diseases - Sandanamsamy, Sylvia Sandanasamy (2020)
Dengue (DENV) and hepatitis C viruses (HCV) are from the Flaviviridae family. DENV causes 50 -100 million dengue hemorrhagic fever or dengue shock syndrome with more than 20, 000 deaths globally. While HCV causes chronic liver diseases to 150 million people globally. Up to date there is no antiviral drug for DENV while HCV antivirals are performing below par. In the search for an antiviral drug for HCV and DENV, extracts from Malaysian fungal isolates were tested. Fifty five fungal isolates were fermented separately on three different media namely, potato dextrose broth (PDB), complex media without phenylacetic acid (CM) and complex media with phenylacetic acid (CM+PA) at 30°C for 5 days. Mycelia-free supernatants were extracted (1:1) using methanol and ethyl acetate which produced 165 methanolic and 165 ethyl acetate crude extracts. Crude extracts (73 ethyl acetate and 61 methanolic) were subjected to HCV NS3/NS4A protease assay and extract with more than 95% inhibition activity were further fractionated using column chromatography. Determination of inhibition concentration at 50% (IC50), cytotoxicity and Gas Chromatography Mass Spectrometry (GCMS) analysis were performed on best active subfraction. Fungal isolate were identified using 18S rDNA sequencing. Crude extracts (45 ethyl acetate and 37 methanolic) that gave more than 80% HCV protease inhibition coherently were tested for DENV NS2B/NS3 protease inhibition activity. Most active crude extract was further fractionated and subfractions were tested using DENV NS2B/NS3 protease inhibition activity.